Social and Labor Status of University Teachers: Elite Specialists or Precariat? - I. V. Vorobyova (Moscow Polytechnic University, 2022)
The article presents the analysis of the social and labor situation with teachers of Russian universities. The reform and optimization of the sphere of higher education affects the nature and conditions of employment of teachers of Russian universities. There is a lowering in the status and prestige of teaching work. In addition, negative processes are penetrating into the field of education, which make it possible to talk not just about the deterioration of working conditions, but the gradual transformation of highly qualified specialists of higher education into candidates for the precariat. The research is based both on theoretical approaches to the precariat and precarious employment and the results of statistical, analytical reports and data from the All-Russian study "Precariat: A new phenomenon in the socio-economic structure of society". Based on these materials, the most important indicators of precarization of the work of higher education workers have been identified. Objective indicators of precarization of Russian higher school teachers include the uncertainty of the remuneration system, instability and non-guaranteed of employment, overemployment and underemployment, and subjective indicators include a sense of vulnerability, defenselessness, fear of job loss and, as a consequence, unsatisfactory social well-being, leading to a low assessment of one's social position in society.